Bioinformatics-Based Activities in High School: Fostering Students’ Literacy, Interest, and Attitudes on Gene Regulation, Genomics, and Evolution - Martins, Ana; Fonseca, Maria João; Lemos, Marina; Lencastre, Leonor; Tavares, Fernando (Frontiers in Microbiology, 2020)
The key role of bioinformatics in explaining biological phenomena calls for the need to rethink didactic approaches at high school aligned with a new scientific reality. Despite the several initiatives to introduce bioinformatics in the classroom, there is still a lack of knowledge on their impact on students’ learning gains, engagement and motivation. In this study, we detail the effects of four bioinformatics labs tailored for high school biology classes named “Mining the Genome: Using Bioinformatics Tools in the Classroom to Support Student Discovery of Genes” on literacy, interest and attitudes on 387 high-school students. By exploring these labs, students get acquainted with bioinformatics and acknowledge that numerous bioinformatics tools can be intuitive for beginners. Furthermore, introducing comparative genomics in their learning practices contributed for a better understanding of curricular contents regarding the identification of genes, their regulation and how to make evolutionary assumptions. Following the intervention students were able to pinpoint bioinformatics tools required to identify genes in a genomics sequence and, most importantly, they were able to solve genomics-related misconceptions. Overall, students revealed a positive attitude regarding the integration of bioinformatics-based approaches in their learning practices, reinforcing their added value in educational approaches.